2020
DOI: 10.1186/s12913-020-4964-6
|View full text |Cite
|
Sign up to set email alerts
|

Using intervention mapping to develop an outpatient nursing nutritional intervention to improve nutritional status in undernourished patients planned for surgery

Abstract: Getty Huisman-de Waal 2 and On the behalf of the Basic Care Revisited (BCR) Research group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…In step 1, the needs assessments showed that in addition to patients, healthcare professionals and relatives were also important target groups to address in the intervention. Nutrition is described as a core area of nursing care [51], which contrasts with the insufficient delivery of nutritional care that we identified, and which is also reported in several other studies [19,32]. In alignment with Noort et al, who developed a nutritional intervention for an anesthesia outpatient clinic [19], we developed a program for education and training for nursing staff to ensure intervention delivery.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In step 1, the needs assessments showed that in addition to patients, healthcare professionals and relatives were also important target groups to address in the intervention. Nutrition is described as a core area of nursing care [51], which contrasts with the insufficient delivery of nutritional care that we identified, and which is also reported in several other studies [19,32]. In alignment with Noort et al, who developed a nutritional intervention for an anesthesia outpatient clinic [19], we developed a program for education and training for nursing staff to ensure intervention delivery.…”
Section: Discussionmentioning
confidence: 73%
“…Nutrition is described as a core area of nursing care [51], which contrasts with the insufficient delivery of nutritional care that we identified, and which is also reported in several other studies [19,32]. In alignment with Noort et al, who developed a nutritional intervention for an anesthesia outpatient clinic [19], we developed a program for education and training for nursing staff to ensure intervention delivery. The logic models (steps 1 and 2) emphasized that in addition to the nutrition perspective, it was important to enhance nursing staff 's knowledge, skills, and attitudes regarding patient involvement.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Generally physical exercise is a crucial factor in multidisciplinary cancer care [25]. But the implementation of a nutritional and psychological intervention into a prehabilitation program may impact clinical outcomes [26][27][28]. Multimodal prehabilitation can include a broad spectrum of interventions like: general conditioning exercises, targeted exercises, nutritional interventions, psychological interventions, smoking cessation, and education [18].…”
Section: Types Of Prehabilitationmentioning
confidence: 99%